Sintering resistant Ni nanoparticles exclusively confined within SiO2 nanotubes for CH4 dry reforming. Issue 13 (15th June 2018) - Li, Ziwei; Wang, Zhigang; Jiang, Bo; Kawi, Sibudjing
Abstract : Ni nanoparticles are exclusively confined within the channels of SiO2 nanotubes (NTs) using the Ni phyllosilicate@SiO2 nanocomposite as a precursor where Ni phyllosilicate will in situ decompose into Ni nanoparticles within SiO2 shell NTs, exhibiting good sintering and carbon resistance for CO2 reforming of CH4 reaction. Abstract : Confining nanoparticles within the channels of one dimensional nanotubes (1D NTs) is one of the effective measures to design sintering resistant catalysts. To achieve this goal, improving the infiltration efficiency of metal precursors into the channels of 1D NTs has been regarded as one of the key issues. Herein, a novel method has been developed to exclusively confine Ni nanoparticles within SiO2 NTs using Ni phyllosilicate (NiPhy) NTs@SiO2 core shell nanocomposites as precursors, where NiPhy NTs will in situ decompose into Ni nanoparticles within the SiO2 shell NTs upon reduction under H2 at 700 °C. Strong interactions between Ni and the SiO2 NT shell, the confinement effect and the hindrance effect provided by the SiO2 nanoparticles sitting among the Ni nanoparticles within the channel of SiO2 NTs prevent the sintering of Ni nanoparticles. These nanocomposites show good catalytic performance and carbon resistance for CO2 reforming of CH4 reaction to produce synthesis gas. This novel method can be easily applied to design other sintering resistant catalysts with exclusive confinement of other metals (M = Co, Fe, Cu etc. ) within the channels of SiO2 NTs for other applications.